Determinan Akuntabilitas Laporan Keuangan: Tinjauan Pada Kinerja dan Politik di Pemerintahan Daerah di Indonesia - Pratolo, Suryo; Diah Irmawati, Febriana (E-Jurnal Akuntansi; Vol 30 No 3 (2020)DO - 10.24843/EJA.2020.v30.i03.p20, 2020)
This study is reviewed and tested empirically the influence of financial performance, dynastic politics, and performance of local government on accountability of regional financial reporting. This study uses the documentation method with secondary data taken from sources of the Indonesian Supreme Audit Board (BPK RI) and the Ministry of Home Affairs. The analytical test tool used in this study is multiple linear regression. It was found that the fiscal decentralization did not significantly affect the accountability of regional financial reporting but it was found that processing results showed a dependency ratio that had a negative and significant effect on the accountability of financial reporting produced by the local government. In the aspect of political dynasties, this variable was found to have no significant effect on the accountability of regional government financial reporting. The results also showed a significant positive effect of local government performance on the accountability of local government financial reporting. Keywords: Financial Performance; Political Dynasty; Performane of Local Government; Accountability of Financial Reporting in Local Governance.